Behavior and Determinants of Public Savings in Commercial Banks in Indonesia: A Dynamic Model Approach - Tri Oldy Rotinsulu; Paulus Kindangen; Hanly Fendy DJohar Siwu (CV. Sakura Digital Nusantara, 2026)
Purpose – This study evaluated the impact of macroeconomic determinants (Bank Indonesia policy interest rate, commercial bank deposit rate, national inflation rate) and demographic shifts (productive-age population) on public savings within Indonesian commercial banks. To resolve frequency discrepancies between annual demographic and quarterly macroeconomic data, a static temporal disaggregation procedure was applied. Design/methodology/approach – The empirical analysis utilized a quantitative time-series dataset spanning an eight-year observation period from 2016 to 2023. A dynamic Error Correction Model (ECM) accommodated short-term behavioral responses while simultaneously capturing long-term structural equilibrium adjustments. Finding/Results – The estimation established that policy and deposit interest rates yielded statistically insignificant impacts on public savings across both temporal horizons. In contrast, the national inflation rate exerted a negative and significant influence on deposit volumes. Furthermore, a larger working-age population exhibited a positive and significant effect on long-term capital accumulation. The dynamic framework confirmed a negative Error Correction Term, proving that savings behavior requires a transitional phase to correct temporal deviations following macroeconomic shocks. Originality/Value – Policymakers must transition from isolated monetary rate manipulations toward integrated macroeconomic and demographic strategies. Synchronizing inflation control mechanisms with long-term demographic planning provides a robust foundation for institutional funding, demonstrating that structural economic stability dictates saving capacities more decisively than traditional yield incentives.